Characterization of a Genomic Region under Selection in Cultivated Carrot (Daucus carota subsp. sativus) Reveals a Candidate Domestication Gene - Macko-Podgórni, Alicja; Machaj, Gabriela; Stelmach, Katarzyna; Senalik, Douglas; Grzebelus, Ewa; Iorizzo, Massimo; Simon, Philipp W.; Grzebelus, Dariusz (Frontiers in Plant Science, 2017)
Carrot is one of the most important vegetables worldwide, owing to its capability to develop fleshy, highly nutritious storage roots. It was domesticated ca. 1,100 years ago in Central Asia. No systematic knowledge about the molecular mechanisms involved in the domestication syndrome in carrot are available, however, the ability to form a storage root is undoubtedly the essential transition from the wild Daucus carota to the cultivated carrot. Here, we expand on the results of a previous study which identified a polymorphism showing a significant signature for selection upon domestication. We mapped the region under selection to the distal portion of the long arm of carrot chromosome 2, confirmed that it had been selected, as reflected in both the lower nucleotide diversity in the cultivated gene pool, as compared to the wild (πw/πc = 7.4 vs. 1.06 for the whole genome), and the high FST (0.52 vs. 0.12 for the whole genome). We delimited the region to ca. 37 kb in length and identified a candidate domestication syndrome gene carrying three non-synonymous single nucleotide polymorphisms and one indel systematically differentiating the wild and the cultivated accessions. This gene, DcAHLc1, belongs to the AT-hook motif nuclear localized (AHL) family of plant regulatory genes which are involved in the regulation of organ development, including root tissue patterning. AHL genes work through direct interactions with other AHL family proteins and a range of other proteins that require intercellular protein movement. Based on QTL data on root thickening we speculate that DcAHLc1 might be involved in the development of the carrot storage root, as the localization of the gene overlapped with one of the QTLs. According to haplotype information we propose that the ‘cultivated’ variant of DcAHLc1 has been selected from wild Central Asian carrot populations upon domestication and it is highly predominant in the western cultivated carrot gene pool. However some primitive eastern landraces and the derived B7262 purple inbred line still carry the ‘wild’ variant, reflecting a likely complexity of the genetic determination of the formation of carrot storage roots.